Bibliometric analysis of Spanish doctoral theses on breastfeeding, between the years 1980-2015 - Ana García Rubio; Carmen Isabel Gómez García; Pilar Martínez Clares; María Jesús Ruíz García (Universidad de Alicante, 2019)
The current society inserted in a VUCA world (volatile, uncertain, complex and ambiguous) has produced vertiginous changes in relation to breastfeeding. That is why we consider it necessary to analyze the knowledge and scientific production carried out to date on this discipline. From this concern, this research emerges as an interdisciplinary study that aims to give priority to the protection, promotion and support of breastfeeding. The purpose is to investigate the growth and distribution of scientific documents through their analysis and evaluation, in order to gather the scientific production of researchers on breastfeeding. To this end, a sample of 155 Doctoral Theses published in Spanish Universities is used, with the common denominator of the word breastfeeding, in the period that goes from 1980 to 2015. The methodology used is mixed, with qualitative data analysis, framed within a retrospective and descriptive analysis, as well as a quantitative analysis through bibliometric indicators. The aim is to offer a solid and reliable set of systematic, empirical and critical research processes and results, in order to present information on current and future research and innovation trends.